2021
DOI: 10.1182/blood.2020005846
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of PET-guided radiation in patients with advanced-stage diffuse large B-cell lymphoma treated with R-CHOP

Abstract: Consolidative radiation therapy (RT) for advanced-stage diffuse large B-cell lymphoma (DLBCL) remains controversial with routine practice continuing to include RT in patients with initial bulky disease or residual masses. PET-CT is a sensitive modality for detecting the presence of residual disease at end-of-treatment (EOT). A PET-guided approach to selectively administer RT has been policy in BC since 2005. Patients with advanced-stage DLBCL diagnosed between January 2005 - March 2017 treated with at least 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 51 publications
3
46
0
2
Order By: Relevance
“…The decreasing utilization of RT in PT-DLBCL over the past 2 decades might be associated with the individualized treatment strategies based on PET-CT and concern of RT related toxicities. The routine practice is to administer consolidative RT to those with positive end-of-treatment PET-CT based on available evidence [ 36 , 37 ]. As a result, post-chemotherapy PET-CT can better define subgroups that could benefit from RT and avoid over-treatment with RT utilization [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreasing utilization of RT in PT-DLBCL over the past 2 decades might be associated with the individualized treatment strategies based on PET-CT and concern of RT related toxicities. The routine practice is to administer consolidative RT to those with positive end-of-treatment PET-CT based on available evidence [ 36 , 37 ]. As a result, post-chemotherapy PET-CT can better define subgroups that could benefit from RT and avoid over-treatment with RT utilization [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In advanced stage HL, the prospective, randomized controlled HD15 trial demonstrated that radiotherapy can be restricted to 11% of patients after effective first-line chemotherapy based on the presence or absence of FDG-avid residual disease (level 5 evidence) [18]. Subsequent randomized controlled trials showed that a favorable PET result also allows a reduction of chemotherapy in advanced-stage HL [15,19], may allow further de-escalation in selected patients in early stages of HL [20,21], and can reliably guide selective administration of consolidative radiotherapy in advancedstage diffuse large B-cell lymphoma (each level 5 evidence) [22].…”
Section: Pet In Lymphomamentioning
confidence: 99%
“…84,85,111,113,[126][127][128][129][130][131][132] RT alone may salvage a proportion of patients with a residual PET-positive site. 133…”
Section: Advanced Dlbcl Key Evidencementioning
confidence: 99%